2015
DOI: 10.1016/j.pnpbp.2015.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the dopamine β-hydroxylase (DβH) inhibitor nepicastat in participants who meet criteria for cocaine use disorder

Abstract: In the present study, we tested the hypothesis that the potent and selective dopamine-β-hydroxylase (DβH) inhibitor nepicastat would have minimal effects on cardiovascular and pharmacokinetic parameters associated with cocaine administration and would reduce the positive subjective effects produced by cocaine. We conducted a double-blind, placebo-controlled, inpatient study of oral nepicastat (0, 80 and 160 mg) concurrent with intravenous (IV) cocaine (0, 10, 20 and 40 mg) in non-treatment seeking participants… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 54 publications
0
6
0
Order By: Relevance
“…The effectiveness of drugs to treat PTSD is being challenged (Ipser and Stein, 2012) and there are evidence-based suggestions that psychotherapy decreases rather than remits PTSD symptoms (Steenkamp and Litz, 2013). In a previous study, safety analyses showed that nepicastat was well-tolerated in healthy adults and no differences in adverse events were observed (De La Garza et al, 2015). Our study showed that nepicastat treatment might be effective in reducing PTSD symptoms in a PTSD mice model with increased catecholamine levels (AD and NA; Martinho et al, 2020), and thus could be an efficient treatment at least in humans with PTSD that have increased catecholamine plasma levels.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness of drugs to treat PTSD is being challenged (Ipser and Stein, 2012) and there are evidence-based suggestions that psychotherapy decreases rather than remits PTSD symptoms (Steenkamp and Litz, 2013). In a previous study, safety analyses showed that nepicastat was well-tolerated in healthy adults and no differences in adverse events were observed (De La Garza et al, 2015). Our study showed that nepicastat treatment might be effective in reducing PTSD symptoms in a PTSD mice model with increased catecholamine levels (AD and NA; Martinho et al, 2020), and thus could be an efficient treatment at least in humans with PTSD that have increased catecholamine plasma levels.…”
Section: Discussionmentioning
confidence: 99%
“…Thirdly, our sample size was small for a molecular genetic study; thus, replication of these findings will be needed to confirm these findings. Future studies could examine the subjective effects of several different doses a day (e.g., 0, 10, 20, and 40 mg; De La Garza et al , 2015). …”
Section: Discussionmentioning
confidence: 99%
“…The 40 mg dose of cocaine was selected on the basis of several prior publications from our lab and others showing that it engenders significant increases in cardiovascular responses and subjective effects, yet the dose is well within the range of doses that can be safely administered to cocaine-dependent patients in a clinical setting. [35,36,37] Each individual participated in both conditions, one dose given at 9 AM and the second at ~1 PM. Subjective effects were recorded 15 minutes prior to and at 5, 10, 15, and 20 minutes after administration.…”
Section: Methodsmentioning
confidence: 99%